(untitled) (International Journal of Nursing Education, 2019)
Introduction: Tuberculosis is a contagious disease, caused by acid fast bacilli. Tuberculosis being a communicable disease has spread and made many people it’s victim. Now it’s high time to do something to control the spread of the disease by spreading awareness about its prevention and about its accessible treatment available. Aim: The aim of this study is to find the level knowledge regarding Tuberculosis among males aged between 20-50 years in rural areas of Moradabad and also to find out the associations between level of knowledge with selected demographic variables. Methodology: Types of studies- Descriptive survey design. Types of participants- Males of 20-50 years residing in rural area. Setting- Selected rural area of Bagadpur, Moradabad Outcome- Based on the findings and interpretation of the present study, the following conclusion was drawn that 32 (53.3%) had average level of knowledge and there is no significant association of level of knowledge with selected demographic variable.